Penerapan Model Pembelajaran Problem Solving dengan Pendekatan Saintifik Untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa - Hasanah, Rofiatun (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2021)
This research was conducted to know the effect from the implementation of the problem solving learning model with a scientific approach to increase the students activities and learning outcomes of class VII MTs. Miftahul Ulum on Integer Number Material. The method used is qualitative and quantitative methods. Collecting data using student and teacher observations, tests, interviews and documentation, the research sample was selected from popolation based on student learning outcomes data at MTs Miftahul Ulum. Based on the study of student learning outcomes using the Problem Solving learning model with the Scientific Approach on the integer material, there was an increase seen in the student's score which increased in the pre-cycle the average score of students was 61.3 with 33.3% classical completeness, the first cycle of the average value The students 'average score was 73.3 with classical completeness 53.3%, in the second cycle the students' average score was 86.7 with 100% classical completeness. As well as the percentage increase in classical student activity in the pre-cycle is still 50%, the first cycle increases 75%, and in the second cycle it reaches 100%. This proves that Problem Solving learning with the Scientific Approach can improve student learning outcomes, with the conclusion that there is an increase in activity and learning outcomes in the application of the Problem Solving learning model with a Scientific Approach to students on integer material class VII MTs miftahul ulum.